2021
DOI: 10.1136/bmjresp-2021-001020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary function in adolescent patients with pectus excavatum or carinatum

Abstract: BackgroundPectus excavatum (PE) and pectus carinatum (PC) have generally been considered an aesthetic issue, although there is growing evidence of associated cardiopulmonary function (CPF) impairment, especially in PE patients. The study goal was to determine any correlation between pectus malformations and cardiopulmonary symptoms and function based on systematic assessment of CPF and thoracic measurements, such as Haller Index (HI) and sternal torsion angle (STA).MethodsData from 76 adolescent patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…[19] In another study, low lung volumes were found in 23% of PE patients. [16] Consistent with the literature, in our patient group, the FVC and FEV1 values were found to be below normal in Groups 2 and 3. In our study, the values of FEV1 and FVC statistically significantly decreased, as the HI increased.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[19] In another study, low lung volumes were found in 23% of PE patients. [16] Consistent with the literature, in our patient group, the FVC and FEV1 values were found to be below normal in Groups 2 and 3. In our study, the values of FEV1 and FVC statistically significantly decreased, as the HI increased.…”
Section: Discussionsupporting
confidence: 92%
“…[7] In a large-volume study in the literature, 62% reported dyspnea and 32% had chest pain at rest. [15] In a recent study by Ramadan et al, [16] 13.3% of patients reported dyspnea while exercising and 20% reported chest pain at rest. The most common complaints in our study were chest pain and shortness of breath, particularly with exercise.…”
Section: Discussionmentioning
confidence: 92%
“…One study was identified by backward citation. Eventually, 48 studies were included: 19 in category I [ 5 , 9 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] ], 21 in category II [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , and 8 in category III [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] ( Figure 1 ).
Figure 1 PRISMA 2020 flow diagram of identification, screening, and inclusion of papers in the 3 categories.
…”
Section: Resultsmentioning
confidence: 99%
“…Combining categories I and II, 31 studies reported a prevalence of scoliosis in PD populations (Appendix C). In all, 19 comprised solely PE cases [ 18 , 19 , [21] , [22] , [23] , 26 , 30 , 31 , 34 , 36 , [38] , [39] , [40] , [41] , [42] , 45 , 47 , 49 , 50 ], 2 solely PC cases [ 35 , 44 ], and 6 analyzed PE and PC separately [ 5 , 16 , 35 , 43 , 46 , 51 , 52 ]. Fourteen studies described definitions of scoliosis or its diagnostic measures [ 5 , 18 , 19 , 22 , 23 , 26 , 30 , 31 , 33 , 34 , 40 , 47 , 52 , 53 ], 9 involved an entire idiopathic population [ 16 , 19 , 22 , 26 , 30 , 31 , 34 , 41 , 51 , 52 ], and 1 a non-surgical one [53] .…”
Section: Resultsmentioning
confidence: 99%
“…2 Patients may also have a reduced forced vital capacity and forced expiratory volume with the potential for right heart failure. 3 Surgical correction of pectus excavatum is invasive and painful, involving the insertion of a substernal titanium bar. 2 Treatment is generally reserved for younger patients, as well as those with severe cardiac or respiratory compromise.…”
mentioning
confidence: 99%